Detonography: Making of renaissance mine (Rudarsko-geološko-naftni zbornik, 2017)
Using the force of explosive authors had made a print of the picture of Renaissance mine onto an aluminium plate. This technique is called Detonography. It has been introduced and developed by Evelin Rosenberg with a number of her colleagues/co-workers, based on “Munroe effect”. To determine the optimal parameters of blasting and supporting materials a large number of laboratory testing has been made on smaller samples.